An Evaluation of a Biopsychosocial Framework for Health-Related Quality of Life and Disability in Rheumatoid Arthritis - Nicassio, Perry M. (2011)
OBJECTIVE: To examine the relationships between physical, psychological, and social factors and health-related quality of life (HRQOL) and disability in rheumatoid arthritis (RA). METHODS: A sample of 106 patients with rheumatoid arthritis (RA) completed measures of self-reported disease activity and psychosocial functioning, including coping, personal mastery, social network, perceived stress, illness beliefs, the SF-36 and Health Assessment Questionnaire Disability Index (HAQ-DI). In addition, physician-based assessment of disease activity using the Disease Activity Scale (DAS 28) was obtained. Hierarchical multiple regression analyses were used to evaluate the relationships between psychosocial factors and scores on the SF-36 and HAQ-DI. RESULTS: Lower self-reported disease activity and higher active coping were significantly related to SF-36 physical functioning scores, whereas lower self-reported disease activity, higher personal mastery, and lower perceived stress contributed to higher SF-36 mental health functioning. Higher self-reported disease activity and lower helplessness were associated with greater disability as indexed by the HAQ-DI. The DAS 28 was unrelated to these outcomes. CONCLUSIONS: The findings highlight the importance of targeting psychological factors to enhance HRQOL in the clinical management of RA patients.